2013
DOI: 10.1038/cr.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

L-glutamine provides acid resistance for Escherichia coli through enzymatic release of ammonia

Abstract: Bacteria, exemplified by enteropathogenic Escherichia coli (E. coli), rely on elaborate acid resistance systems to survive acidic environment (such as the stomach). Comprehensive understanding of bacterial acid resistance is important for prevention and clinical treatment. In this study, we report a previously uncharacterized type of acid resistance system in E. coli that relies on L-glutamine (Gln), one of the most abundant food-borne free amino acids. Upon uptake into E. coli, Gln is converted to L-glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
197
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(216 citation statements)
references
References 29 publications
16
197
3
Order By: Relevance
“…After acid exposure, the intracellular pH decreases, and DNA is damaged. The cells can resist the acid stress through a variety of defence mechanisms, such as regulating the flow of protons inside and outside cells [11,13] and neutralizing intracellular protons through producing alkaline compounds [40]. Further, the DNA repair enzyme system can also assist cells to resist acid stress through repair of the damaged DNA [12].…”
Section: Discussionmentioning
confidence: 99%
“…After acid exposure, the intracellular pH decreases, and DNA is damaged. The cells can resist the acid stress through a variety of defence mechanisms, such as regulating the flow of protons inside and outside cells [11,13] and neutralizing intracellular protons through producing alkaline compounds [40]. Further, the DNA repair enzyme system can also assist cells to resist acid stress through repair of the damaged DNA [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the catabolic glycine decarboxylase pathway similarly serves to buffer the cytoplasm via the release of ammonia during glycine decarboxylation. Indeed, Lu et al recently demonstrated that the conversion of glutamine to glutamate, with the release of ammonia, can serve a protective role for E. coli during exposure at pH 2.5 (59).…”
Section: Figmentioning
confidence: 99%
“…Strains were cultured overnight in LB medium (10 g/liter tryptone, 5 g/liter yeast extract, 100 mM NaCl) buffered with 100 mM MES, pH 5.5. Glutamine (10 mM), which the bacteria convert to glutamate, the substrate of glutamate decarboxylase (86), was included. For anaerobic culture, closed 9-ml screw-cap tubes nearly full of medium were incubated for 18 h at 37°C.…”
Section: Figmentioning
confidence: 99%